Accessing Organizational Performance through Agile Methodologies in Aluminum Manufacturing Firms in Delta State, Nigeria - Efe-Eyefia Oghenechoja; Okolie Ugo Chuks; Oneh Uwabunkonye Festus (CV. Tripe Konsultan, 2025)
This study looked at assessing organizational performance through agile methodologies within selected Aluminium manufacturing firms in Delta State, Nigeria. The specific objectives were to: examine the effect of Agile Iterative Development on organisational performance, assess the influence of Agile Collaboration and Communication on organisational performance, determine the effect of Agile Adaptive Planning on organisational performance, and evaluate the contribution of Agile Continuous Integration and Testing to organisational performance. A sample size of 300 respondents was selected, and 287 valid questionnaires were analysed using descriptive statistics, correlation, and regression techniques. The findings revealed that all four Agile dimensions, AID, ACC, AAP, and ACIT, had positive and significant effects on organisational performance. AID enhanced operational efficiency through improved feedback cycles; ACC strengthened teamwork and communication, thereby improving production flow; AAP enabled firms to respond quickly to disruptions and market fluctuations; and ACIT improved quality consistency through early error detection and frequent system integration. Regression results further showed that the combined agile variables explained a substantial proportion of the variance in organisational performance, indicating their strong predictive power. The study concludes that agile methodologies significantly enhance productivity, adaptability, quality assurance, and overall performance in Aluminium manufacturing firms. It recommends that firms strengthen iterative processes, adopt digital communication systems, institutionalise flexible planning frameworks, and implement continuous integration and testing mechanisms to improve efficiency and competitiveness.